2020
DOI: 10.1017/s0022149x2000036x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring species diversity of lissorchiid trematodes (Digenea: Lissorchiidae) associated with the gravel snail,Lithoglyphus naticoides, in European freshwaters

Abstract: Comparative analysis using complete ITS2 and partial 28S rDNA sequence data revealed that cercariaeum developing in rediae in Lithoglyphus naticoides represent two different lissorchiid species. One morphotype of cercariaeum is conspecific with adult Palaeorchis incognitus from European roach, Rutilus rutilus. The other cercariaeum is attributable to the genus Asymphylodora, but the species identity is not yet determined. We also generate the first rDNA sequences for Asymphylodora progenetica based on new coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…Phylogenetic data support the unification of the lissorchiine and the asymphylodorine digeneans into the same family but do not support the monophyly of the Lissorchiinae ( [9][10][11]40], Present Study). Notably, the position of two lissorchiine genera, Lissorchis and Palaeorchis Szidat, 1943, is unstable in the phylograms of different authors [10,11], Present Study. Anarhichotrema, in contrast to the other lissorchiid genera, has a marine life history and the filamented eggs compare with [5,9,11].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Phylogenetic data support the unification of the lissorchiine and the asymphylodorine digeneans into the same family but do not support the monophyly of the Lissorchiinae ( [9][10][11]40], Present Study). Notably, the position of two lissorchiine genera, Lissorchis and Palaeorchis Szidat, 1943, is unstable in the phylograms of different authors [10,11], Present Study. Anarhichotrema, in contrast to the other lissorchiid genera, has a marine life history and the filamented eggs compare with [5,9,11].…”
Section: Discussioncontrasting
confidence: 58%
“…The division is based on the number of testes: two in the former and one in the latter subfamily [5]. Phylogenetic data support the unification of the lissorchiine and the asymphylodorine digeneans into the same family but do not support the monophyly of the Lissorchiinae ( [9][10][11]40], Present Study). Notably, the position of two lissorchiine genera, Lissorchis and Palaeorchis Szidat, 1943, is unstable in the phylograms of different authors [10,11], Present Study.…”
Section: Discussionmentioning
confidence: 75%
“…Genomic DNA was isolated from ethanol-fixed specimens according to Stunžėnas' protocol (Stunžėnas et al, 2011;Petkevičiūtė et al, 2014). Amplification of the two rDNA regions was performed following the protocol used in our previous studies (Petkevičiūtė et al, 2014(Petkevičiūtė et al, , 2020. The ITS2 was amplified using the forward primer 3S (5 ′ -CGG TGG ATC ACT CGG CTC GTG-3 ′ ) (Bowles et al, 1995) and the reverse primer ITS2.2 (5 ′ -CCT GGT TAG TTT CTT TTC CTC CGC-3 ′ ) (Cribb et al, 1998).…”
Section: Molecular Sequencing and Phylogenetic Analysesmentioning
confidence: 99%
“…The clarification of phylogenetic relationships of trematodes today undoubtedly depends on molecular markers. Unfortunately, a comprehensive molecular phylogenetic analysis of relationships between lissorchiids is lacking, as only a few species were available for previous studies (Besprozvannykh et al, 2012; Sokolov & Gordeev, 2019; Petkevičiūtė et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…recorded a cercaria of this type from B. funiculata in Thailand. Other previous reports of lissorchiid cercariae from bithyniid species includePetkevičiūtė et al (2020) andSchwelm et al (2020), both from Europe, andBesprozvannykh et al (2012) in the Russian Far East.Wiroonpan et al (2021) reported mutabile cercariae to be common in B. s. siamensis in the vicinity of Bangkok. Their ITS2 sequence for one of these (MW020049) had only partial coverage (72%) and low similarity (77%) with our mutabile sequence, suggesting that they are not conspecific.…”
mentioning
confidence: 92%